THE URGENCY OF HUMAN RIGHTS PROTECTION AGAINST NATURAL RESOURCE CONFLICTS IN RAJA AMPAT PAPUA - Ikmah Wati; Anis Salsabila; Anissa Nuraeni Maulani; Hilma Hilwana (Jurnal Kewarganegaraan, 2026)
The Raja Ampat Islands are famous for the richest marine biodiversity in the world, but in reality the exploitation of natural resources, especially nickel mining has damaged the environment and has become a serious threat to the marine ecosystem and the rights of indigenous peoples. The urgency of human rights protection against natural resources in Raja Ampat Papua, is something that must be done. The purpose of this study is to examine the root of conflict problems in Raja Ampat, analyze the impact of conflict from natural resources that have occurred, and evaluate the role of government in providing human rights protection against natural resource conflicts in Raja Ampat. This study uses a qualitative approach with a case study design to understand the phenomenon of conflict that occurs in Raja Ampat Papua. Secondary data sources are used in this study from various books, journal articles, and policy studies. Natural resource conflicts in Raja Ampat, especially those related to the expansion of nickel mining continue to increase sharply, causing damage to forests, sea sedimentation, and threatening biodiversity, and cause social inequality for people in Raja Ampat. The conflict has a serious impact on social aspects, threatened tourism sectors, and severe ecological damage. There is a gap in government policy related to mining licensing and natural resource governance in Raja Ampat Papua. The government needs to increase the mechanism of law enforcement to ensure the protection of human rights related to the management of natural resources. Supervision and accountability need to emphasize the transparency of natural resource management to prevent the exploitation of natural resources that violate human rights.